Mechanism of β4 Subunit Modulation of BK Channels - Wang, Bin (The Rockefeller University Press, 2006)
Large-conductance (BK-type) Ca2+-activated potassium channels are activated by membrane depolarization and cytoplasmic Ca2+. BK channels are expressed in a broad variety of cells and have a corresponding diversity in properties. Underlying much of the functional diversity is a family of four tissue-specific accessory subunits (β1–β4). Biophysical characterization has shown that the β4 subunit confers properties of the so-called “type II” BK channel isotypes seen in brain. These properties include slow gating kinetics and resistance to iberiotoxin and charybdotoxin blockade. In addition, the β4 subunit reduces the apparent voltage sensitivity of channel activation and has complex effects on apparent Ca2+ sensitivity. Specifically, channel activity at low Ca2+ is inhibited, while at high Ca2+, activity is enhanced. The goal of this study is to understand the mechanism underlying β4 subunit action in the context of a dual allosteric model for BK channel gating. We observed that β4's most profound effect is a decrease in Po (at least 11-fold) in the absence of calcium binding and voltage sensor activation. However, β4 promotes channel opening by increasing voltage dependence of Po-V relations at negative membrane potentials. In the context of the dual allosteric model for BK channels, we find these properties are explained by distinct and opposing actions of β4 on BK channels. β4 reduces channel opening by decreasing the intrinsic gating equilibrium (L0), and decreasing the allosteric coupling between calcium binding and voltage sensor activation (E). However, β4 has a compensatory effect on channel opening following depolarization by shifting open channel voltage sensor activation (Vho) to more negative membrane potentials. The consequence is that β4 causes a net positive shift of the G-V relationship (relative to α subunit alone) at low calcium. At higher calcium, the contribution by Vho and an increase in allosteric coupling to Ca2+ binding (C) promotes a negative G-V shift of α+β4 channels as compared to α subunits alone. This manner of modulation predicts that type II BK channels are downregulated by β4 at resting voltages through effects on L0. However, β4 confers a compensatory effect on voltage sensor activation that increases channel opening during depolarization.